Hybrid framework for detection of human face based on haar-like feature - Ramkumar, G; Logashanmugam, E (International Journal of Engineering and Technology, 2018)
Augmentation in computer technology has made attainable to prompt incipient video processing practices in territory of biometric identification. Applications embroil face detection and face recognition consolidated to examination framework, signal investigation etc. Face detection is broadly utilized as a part of intuitive user interfaces and assumes an essential part in the area of computer vision. In order to build a fully automated system that can analyze the information in face image, there is a requirement for powerful and productive face detection algorithms. In this paper a framework is proposed for human face detection in images acquired under various illumination conditions. The features established on Gabor filters extracted from local image are applied to be the input of the Haar like classifier. At last, the experiment indicates elite in both accuracy and speed of the created framework.Â Â